Evaluation of reporting trends in the MAUDE Database: 1991 to 2022 - Meital Mishali; Nadav Sheffer; Oren Mishali; Maya Negev (Digital Health)
Adverse event reporting for medical devices is critical for risk mitigation. The Food and Drug Administration's (FDA) Manufacturer and User Facility Device Experience (MAUDE) database serves as a key tool for post-market surveillance, receiving reports from various sources. Ensuring information integrity, especially across diverse reporting sources, is paramount. Periodic regulatory updates aim to enhance reporting. Objective Analyze reporting patterns, assess the potential contribution of 2015 and 2018 regulatory updates on reporting rates for varies reporters. Additionally, evaluating reporting schedule compliance by comparing average reporting times to regulatory requirements for these reporters. Methods Data from 1991–2022 was retrieved from the MAUDE database. Annual report counts were filtered by reporter and event type. Average reporting time was calculated as the difference between received and awareness dates. Results The 2018 Voluntary Malfunction Summary Reporting (VMSR) program correlated with an increase in manufacturers’ event reporting, peaking at 3,135,501 events in 2022. Distributors’ reports surged post-2018, while voluntary reports steadily increased since 1997, spiking notably in 2015 with the Electronic Medical Device Reporting (eMDR) submission update. Reporting times for deaths averaged 80 days for manufacturers, far exceeding regulatory requirements, compared to 40 days for distributors and 46 days for user facilities. Malfunction events had longer average reporting times for manufacturers (89 days) compared to distributors (44 days). Conclusions Changes in reporting trends around 2015 and 2018 may be linked to regulatory updates. Tailoring regulatory changes for each reporter type, like user-friendly electronic forms, new reporting programs, and exemptions cancelations, can improve reporting. Balancing the volume of reports among different reporters is crucial for enhancing database integrity, transparency, and overall health outcomes.